2015
DOI: 10.1001/jamadermatol.2015.0739
|View full text |Cite
|
Sign up to set email alerts
|

Sun Protection and Skin Examination Practices in a Setting of High Ambient Solar Radiation

Abstract: In this large sample exposed to high levels of ambient solar radiation, sun protection and skin examination practices were most frequent among those with a history of treated skin lesions or sun-sensitive skin types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 29 publications
4
28
4
1
Order By: Relevance
“…Nonetheless, the present authors, as well as many evolutionary biologists have concerns about the skin cancer (genotoxic) hypothesis, primarily because the peak incidence of the most common, potentially lethal skin cancer, squamous cell carcinoma, occurs above the age of 70 (Franceschi, Levi, Randimbison, & La Vecchia, ; Ridky, ), well past both the reproductive years (Blum, ; Goding, ; Robins, ) and life expectancy of ancestral hominins (Kennedy, ; Sievert, ; Trinkaus, ). Pertinently, fair‐skinned humans residing near the Equator in Queensland, Australia exhibit much earlier onsets of skin cancer (Olsen, Thompson, Green, Neale, & Whiteman, ), without evidence of a reduction in reproductive success. While the deadliest of skin cancers, melanoma, can occur during childhood and reproductive years, its overall incidence (<2% of all skin cancers) (Jemal, Devesa, Hartge, & Tucker, ; Le et al, ) is likely too uncommon to have exerted an evolutionary influence.…”
Section: Evolution Of Pigmentation In Ancestral Humans—an Updatementioning
confidence: 99%
“…Nonetheless, the present authors, as well as many evolutionary biologists have concerns about the skin cancer (genotoxic) hypothesis, primarily because the peak incidence of the most common, potentially lethal skin cancer, squamous cell carcinoma, occurs above the age of 70 (Franceschi, Levi, Randimbison, & La Vecchia, ; Ridky, ), well past both the reproductive years (Blum, ; Goding, ; Robins, ) and life expectancy of ancestral hominins (Kennedy, ; Sievert, ; Trinkaus, ). Pertinently, fair‐skinned humans residing near the Equator in Queensland, Australia exhibit much earlier onsets of skin cancer (Olsen, Thompson, Green, Neale, & Whiteman, ), without evidence of a reduction in reproductive success. While the deadliest of skin cancers, melanoma, can occur during childhood and reproductive years, its overall incidence (<2% of all skin cancers) (Jemal, Devesa, Hartge, & Tucker, ; Le et al, ) is likely too uncommon to have exerted an evolutionary influence.…”
Section: Evolution Of Pigmentation In Ancestral Humans—an Updatementioning
confidence: 99%
“…Moreover, unlike other pediatric analyses (Whiteman et al, 2005), a higher frequency of daily application of sunscreen was associated with a higher nevus count. As suggested by other studies (Green et al, 2011;Olsen et al, 2015aOlsen et al, , 2015b, the use of high-SPF (>30) sunscreens exclusively, when compared with the use of sunscreens with SPF 30, adequately protected skin during sun exposure and significantly reduced nevus burden.…”
Section: Multivariate Analysismentioning
confidence: 59%
“…Although sunburn early in life increases the lifetime risk of developing melanoma, there is less conclusive evidence regarding the protective role of sun-protection practices and sunscreen use (Autier et al, 2007;Crane et al, 2009;Gorham et al, 2007;Green et al, 2011;Huncharek and Kupelnick, 2002;Køster et al, 2010;Olsen et al, 2015aOlsen et al, , 2015bRadespiel-Tr} oger et al, 2009;Rodvall et al, 2010;United States Environmental Protection Agency, 2011;Wolf et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Reported SSE rates among melanoma survivors vary based on the definition of SSE used and the timeframe of assessment (Coroiu et al, accepted). For example, a large cohort study conducted in Australia (n=1,433 confirmed melanoma cases) found that 57.4 % of participants had performed an SSE in the past 3 years (Olsen et al, 2015). A cross-sectional study found that among 316 melanoma survivors, 28% reported having ever engaged in SSE, 16% reported doing monthly SSE, and 8% reported doing SSE every 2 months (Glenn, Chen, Chang, Lin, & Bastani, 2016).…”
Section: Skin Self-examination (Sse)mentioning
confidence: 99%